2022
DOI: 10.1111/dmcn.15332
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproductive technology: Short‐ and long‐term outcomes

Abstract: In 1978 Louise Joy Brown was the first infant born by in vitro fertilization (IVF), as the result of the pioneering work of Robert Edwards, Patrick Steptoe, and Jean Purdy in the successful development of this procedure. 1,2 This dramatic success was followed 14 years later by the first infant born after intracytoplasmic sperm injection (ICSI), 3 a method that was initially developed for male infertility.These and subsequent advances in the rapidly developing field of assisted reproductive technology (ART) hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 106 publications
0
14
0
1
Order By: Relevance
“…The outcome data of childhood and growth into early adulthood are the potential hotspots and trends of ICSI. Continuous follow-up into later life needs to be investigated and confirmed ( 32 ). Recent studies suggested a small excess of birth defects and low birth weight in children conceived via ART.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome data of childhood and growth into early adulthood are the potential hotspots and trends of ICSI. Continuous follow-up into later life needs to be investigated and confirmed ( 32 ). Recent studies suggested a small excess of birth defects and low birth weight in children conceived via ART.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested a small excess of birth defects and low birth weight in children conceived via ART. Furthermore, several studies have reported an increased frequency of ART conceptions associated with Beckwith–Wiedemann syndrome or Angelman syndrome caused by an imprinting defect ( 32 , 33 ). The keywords with the strongest citation burst result indicated the focus and hotspots of ICSI research, concentrating on the outcomes of pregnancy and risks of live birth from 2014 onward.…”
Section: Discussionmentioning
confidence: 99%
“…Infertility evolved into a profound issue in many countries affecting a significant proportion of individuals of both sexes as the popularity of ART procedures matures and tries to meet the requests. As far as it goes for men, many non(reproductive) disorders and treatments might stand behind this, while a fraction of cases remain unexplained and, thus, a thorough evaluation could guide the clinicians to treatable causes and allow natural fertility [ 191 , 192 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steptoe, enabling a gestational surrogate to carry a child genetically unrelated to the surrogate mother but the intended parent. Then, the first successful gestational surrogacy took place in 1985 (17). ART procedures involve IVF, intracytoplasmic sperm injection (ICSI), cryopreservation of gametes or embryos, and fertility medication.…”
Section: Advances In Artmentioning
confidence: 99%